The Contribution of the Mining Sector to the Economic and Social Development of Mongolia - Davaasuren Avirmed; Khishigjargal Bold (The Mongolian Journal of International Affairs)
The economic and social development of Mongolia is highly dependent on global market conditions, international economic trends, and the environment for foreign investment. The country’s economic growth has primarily relied on the production of the mining and mineral resources sector. The mining sector occupies a significant position in Mongolia’s industrial production. Furthermore, mining and extractive industries make a substantial contribution to tax revenues in Mongolia's unified state budget. Export revenues from products such as copper concentrate, coal, iron ore, and fluorspar play a vital role in funding the state budget.